Review: The Role of Insulin in Aging: Mechanisms, Impact, and Therapeutic Perspectives (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2026)
Aging is characterized by the age-dependent decline of physiologic function that in turn raises susceptibility to death. This process of degeneration is characteristic for all forms of life and constitutes a major driving force behind many diseases including obesity, type 2 diabetes mellitus, Alzheimers disease and heart disease. Failures in insulin, an essential hormone, have been shown to be associated with most of the age-related diseases. Insulin is a critical hormone controlling metabolism, development, cell division and differentiation. It is regulated by two major mechanisms: release and clearance of insulin from the blood as well as sensitivity to a tissue's tissues. Aging disrupts these processes, which contributes to insulin dysfunction, and increases the incidence of disease and death. Insulin action in aging is the purpose of this project, and its contribution to age-related diseases. Also indicate that improving insulin function may be an effective way to promote healthier and longer life.